The Ambition Among Students In The Light Of Some Social Variables (Journal of Human Sciences, 2023)
This research proceeds to achieve a set of goals, including knowing the professional ambition that most of the preparatory education students seek, and identifying the reasons that prompted to draw the features of this ambition, and this study was launched to verify a set of hypotheses, which is the existence of a statistically significant relationship between professional ambition and a set of variables, namely (gender / income / profession of father and mother / level of education of father and mother / student estimate), and the approach used in this study was the survey by sample. Its type was a relative stratified random sample, consisting of 253 items distributed over 6 schools from the city of Ajdabiya, in which the interview form was used, It was fixed with a degree of 0.93 through the use of the Alfacronbach test coefficient and a valid one with a rate of 0.96. With the following variables: (mother and father's occupation - income - mother's level of education) according to the results of the chi-square test. fertile and worthy of scrutiny and scientific scrutiny, and the competent authorities must link between what students aspire to and plans for educational and economic development.